EXPLORING YOUNG CONSUMERS’ BRAND ENGAGEMENT ON SOCIAL MEDIA: THE CASE OF SOCIOLLA THROUGH SELF-DETERMINATION THEORY - Arinto, Boby; Singh, Rajesh Prettypal; Humairoh, Humairoh (Universitas Muhammadiyah Tangerang, 2025)
This study investigates the influence of consumer motivation, based on Self-Determination Theory (SDT), on brand engagement and brand loyalty on social media, with a case study on Sociolla users in Greater Jakarta. A survey was conducted with 130 young female respondents who actively interact with Sociolla’s content on Instagram, TikTok, and other platforms. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. The results indicate that autonomy, competence, relatedness, along with intrinsic and extrinsic motivation, have significant positive effects on brand engagement. Furthermore, brand engagement significantly affects brand loyalty. The model shows strong explanatory power, with R² values of 0.656 for brand engagement and 0.673 for brand loyalty. These findings emphasize the importance of fulfilling consumers’ psychological needs in digital content strategies. This study contributes to SDT-based branding literature and offers practical implications for beauty brands aiming to foster sustained engagement and loyalty in competitive social media environments.